PENGEMBANGAN MEDIA VIDEO ANIMASI MENGENAI PENCEGAHAN DIARE PADA SISWA SEKOLAH DASAR (Jurnal Kesehatan Siliwangi, 2023)
Background: Diarrhea is a health problem in Indonesia and the highest contributor to mortality and morbidity, especially in children. Efforts that can be made by health promoters by providing health education using the media. Animated videos are very suitable for elementary school students because there are pictures and words which when combined in an educational medium can increase children's interest in learning and improve children's memory of the material presented. The development of animated video media regarding the prevention of diarrhea in students is one of the means to obtain information repeatedly and to attract interest in learning. Purpose: To develop and determine the feasibility of animated video media regarding the prevention of diarrhea in students at Rahayu 4 Elementary School, Bandung Regency. Methods: This type of research uses R&D (Research and Development). This study uses a total sampling as many as 38 grade 5 students. Results: Based on the analysis of student needs, animated videos on diarrhea prevention became the preferred media by paying attention to media content including moving cartoon characters, bright colors, 2-5 minutes of video duration, and easy-to-understand language. , simple, legible letters. Making animated video media based on the 5 stages of the ADDIE development model. The results of the feasibility of the media obtained based on material experts by 88%, media experts by 95% and users, namely students by 86%. Conclusion: Animated video media is declared very suitable to be used as an educational medium. Recommendation: Further tests can be conducted to determine the effectiveness of using animated video media regarding the prevention of diarrhea in students.